Assessment of cardiac angle in fetuses with congenital heart disease at risk of 22q11.2 deletion. (2nd December 2015) - Vigneswaran, T. V.; Kametas, N. A.; Zinevich, Y.; Bataeva, R.; Allan, L. D.; Zidere, V.
Abstract: Objectives: To evaluate fetal cardiac angle as a screening tool for 22q11.2 deletion among cases with cardiac anomalies known to be associated with this genetic condition, to examine the correlation of fetal cardiac angle with thymic–thoracic (TT)‐ratio, and to assess the performance of TT ratio as a covariate in screening for 22q11.2 deletion. Methods: This was a retrospective cohort study that reviewed the records of 74 cases with cardiac anomalies known to be associated with 22q11.2 deletion (tetralogy of Fallot, common arterial trunk, interrupted aortic arch and right aortic arch) that were diagnosed between 2007 and 2013. The karyotype was known in all cases. The fetal cardiac angle and TT‐ratio were measured using stored three‐dimensional spatiotemporal image correlation volume datasets and compared in those with del.22q11.2 and those without. Results: Of the 74 cases reviewed, 16 had 22q11.2 deletion. The mean cardiac angle was larger in the cases with 22q11.2 deletion than in those without (68.6° vs 58.7°, respectively; P  = 0.02). Multivariate regression analysis showed an association between cardiac angle and TT‐ratio in fetuses with 22q11.2 deletion ( r 2  = 0.33; P  = 0.02) but not in those with a normal karyotype ( P  = 0.4). Logistic regression analysis demonstrated that fetal cardiac angle, but not TT‐ratio, is an independent predictor of 22q11.2 deletion among fetuses with 22q11.2 deletion‐associated cardiac anomalies ( P  = 0.02; area under the receiver–operating characteristics curve = 0.69). Conclusions: An enlarged fetal cardiac angle is an independent predictor of 22q11.2 deletion among fetuses with 22q11.2 deletion‐associated cardiac anomalies. However, its performance as a single variable in a screening model is not sufficient to guide management decisions regarding invasive testing. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.